Molecular Dynamics Studies of Therapeutic Liquid Mixtures and Their Binding to Mycobacteria - Monteiro, Hugo; Santos, Filipa; Paiva, Alexandre; Duarte, Ana Rita C.; Ferreira, Ricardo J. (Frontiers in Pharmacology, 2021)
Tuberculosis is an highly contagious disease still considered by the World Health Organization as one of most infectious diseases worldwide. The therapeutic approach used to prevent and treat tuberculosis targets the Mycobacterium tuberculosis complex, comprises a combination of drugs administrated for long periods of time, which, in many cases, could cause several adverse effects and, consequently, low compliance of the patient to the treatment and drug-resistance. Therefore, therapeutic liquid mixtures formulated with anti-tuberculosis drugs and/or adjuvants in tuberculosis therapy are an interesting approach to prevent toxic effects and resistance to anti-tuberculosis drugs. The herein formulated therapeutic liquid mixtures, including ethambutol, arginine, citric acid and water under different molar ratios, were studied through a molecular dynamics approach to understand how ethambutol and arginine could be stabilized by the presence of citric acid and/or water in the mixture. To gain insights on how the uptake of these mixtures into the mycobacteria cell may occur and how a mycobacterial ABC transporter could contribute to this transport, multiple simultaneous ligand docking was performed. While the interactions between citric acid and ethambutol involving the carboxyl and hydroxyl groups of citric acid with the amines of ethambutol were identified as the most critical ones. Water molecules present in the mixture provides the necessary network of hydrogen bonds that stabilize the mixture. Molecular docking additionally provided an interesting hypothesis on how the different mixture components may favor binding of ethambutol to an ABC importer. The data presented in this work helps to better understand these mixtures as well as to provide cues on the mechanisms that allow them to cross the mycobacterial cell membrane.